Evaluasi Integrasi ITIL dan COBIT 5 untuk Manajemen Layanan TI ICRM+ - Kusuma Ayu, Karisma; Utomo, Agus Prasetyo; Mariana, Novita (Institut Informatika Dan Bisnis Darmajaya, 2025)
This study evaluates the effectiveness of integrating ITIL and COBIT frameworks in enhancing IT service quality in the